Analysis on Waste to Energy Potential of Padang Municipal Solid Waste for Sustainable Future - Slamet Raharjo; Zagita Andriani Ariska (Universitas Diponegoro, 2022)
Reduce, reuse, recycle (3R), and recovery are types of waste processing regulated in Law No. 18 of 2008. One form of recovery is Waste to Energy (WtE) which is one of the national development priorities. Currently, the implementation of 3R is less than 5% and it has not been implemented at all in Padang City. Therefore, this current research studies the WtE potential of Padang municipal solid waste. The research was conducted by collecting data on the population of Padang City, the generation, composition, and recycling potential of Padang City waste, and the calorific value of each waste composition. This research applies thermal incineration technology with three variations of scenarios. Scenario #1 is a WtE application with 3R based on existing conditions, scenario #2 is a WtE application with 3R based on government targets, and scenario #3 is a WtE application with 3R based on the results of the questionnaire. Scenario #2 is the best one because it considers the WtE idea and community-based 3R recycling in line and continues for better waste management in Padang City. The scenario may produce 394.23 MW of electricity that can serve around 1,329 houses, while also improving the 3R rate of around 1.98% per year.